Design of a Traditional Clothing Rental Information System Using the First Come First Serve (FCFS) Algorithm Based on a Website - Handoyo, Nuh; Nur Laila, Siti (Journal of Artificial Intelligence and Software Engineering, 2025)
This study aims to design and develop a web-based traditional clothing rental information system using the First Come First Serve (FCFS) algorithm to enhance rental management efficiency. The background of this research is based on issues in traditional clothing rental management, which is still conducted manually, leading to booking uncertainties and stock management errors. The research methods include interviews, observations, and literature studies, along with system development using the Waterfall model. The results show that the developed system effectively manages rentals by ensuring orders are processed according to arrival time while providing a responsive and user-friendly interface. The conclusion of this study is that the FCFS-based system improves transparency and fairness in traditional clothing rentals while making it easier for customers to place orders.